Djeliya : a West African fantasy epic - Ba, Juni (Graphic novel author) (TKO Studios, 2021)
"Inspired by West African folklore and stories handed down over centuries, follows the adventures of Mansour Keita, last prince of a dying kingdom, and Awa Kouyaté, his loyal Djeli, or 'royal storyteller' as they journey to meet the great wizard who destroyed their world and then withdrew into his tower, never to be seen again. On their journey they'll cross paths with friend and foe, from myth and legend alike, and revisit the traditions, tales, and stories that gave birth to their people and nurture them still. But what dark secret lies at the heart of these stories, and what purpose do their tellers truly serve?" --